Reframing Fatherhood: Hadith Interpretations and the Digital Discourse on Fatherlessness in Indonesia - Wardah Zairina (Zamzami Scholar Publishing, 2026)
Fathers’ role in the family profoundly impacts children’s character formation, emotional well-being, and moral values through active and consistent involvement. In Indonesia, there is still a view that limits the role of fathers as financial providers, which contributes to the phenomenon of fatherlessness, namely the physical and emotional absence of fathers in the lives of their children. This article analyzes this phenomenon through Norman Fairclough’s critical discourse analysis approach, which explores how the discourse of fatherlessness is formed in the digital space and its influence on public perceptions of fatherhood. The analysis results show that this discourse can potentially shift understanding toward a more egalitarian role for fathers in the family. In addition, hadiths emphasizing the role of fathers as leaders, moral educators, and guides in religious discipline reinforce the position of fathers in parenting that encompasses the moral, spiritual, social, emotional, and academic aspects of children. The comprehensive involvement of fathers can overcome the phenomenon of fatherlessness and support children’s comprehensive development, while changing the paradigm of fathers’ roles in modern families.